How Good at Neurology are you? – Answers. Issue 5 (1st October 2004) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. Ventricular cystic neurocysticercosis. Fig. 1a is a T2-weighted axial scan showing a large, smooth-edged, well-defined cyst in the frontal horn of the left lateral ventricle, together with further smaller cysts in the anterior interhemispheric fissure. There is secondary hydrocephalus. Figures 1b and 1c are T1 weighted coronal scans, pre and post gadolium, respectively. The signal intensity of the cysts is similar to that of CSF and shows no enhancement. These features, together with the clue of her foreign travel, lead to the correct diagnosis of the cystic form of neurocysticercosis. Do not let the fact she is a vegetarian put you off. Contamination of salads through poor horticultural and culinary practices is common. Humans are accidental hosts. Taenia Solium eggs from the pork tapeworm hatch in the stomach and the larvae burrow through the gut wall and disseminate via the circulation, particularly to the brain. The larvae may encyst.